Effects of low- versus high-velocity-loss thresholds with similar training volume on maximal strength and hypertrophy in highly trained individuals - Myrholt, R. B.; Solberg, P.; Pettersen, H.; Seynnes, O.; Paulsen, G. (International Journal of Sports Physiology and Performance, 2023)
In the present intervention study, low-velocity-loss (LVL) versus high-velocity-loss (HVL) thresholds in the squat and bench press were compared for changes in muscle strength, power, and hypertrophy. Methods: Strength-trained volunteers (7 and 9; age: 27.2 [3.4] y; height: 174.6 [8.0] cm; body mass: 75.3 [10.1] kg) were randomized into an LVL or HVL threshold group (LVL n = 3 + 5, and HVL n = 4? + 4?). Training took place 3 times per week over 6 weeks (loads: ~75%-90% of 1- repetition maximum [1RM]). The thresholds of LVLs and HVLs were set at 20% and 40% of maximal velocity, respectively, for the squat, and at 30% and 60%, respectively, for the bench press. Before and after the intervention, 1RM, leg press power, and squat jump were tested. The load (~45% of 1RM) corresponding to 1-m/s velocity was assessed in all sessions for both exercises. In addition, the thickness of the vastus lateralis and triceps brachii and body composition (dual-energy X-ray absorptiometry [DEXA]) were measured. Results: Squat and bench-press 1RM increased similarly in both groups by 7% to 11% (SD: 4%-6%, P < .05). No group differences were obs srved for changes in jump height, leg press power, or DEXA lean mass. However, HVL showed a small increase in muscle thickness of the vastus lateralis compared with LVL (6 ± 6% [95% CI] group difference, P < .05). Conclusion: For strength-trained individuals, high-volume lower-velocity-loss thresholds were as effective as higher thresholds for improvements in 1RM strength; but local hypertrophy was seemingly elicited faster with higher velocity-loss thresholds.